Preliminary Studies on the Quality of Spruce and Silver Fir Seed as affected by its Source - Singh, R. V.; Singh, Virendra (Indian Forester, 1987)
The results of an investigation conducted to study the quality of spruce and silver fir seed as affected by its source in respect of weight, proportion of sound, unsound and empty seeds, absorption of water, germination percentage and germination value are reported. The seed source has been found to affect appreciably all the parameters studied.